Potensi Penyimpangan Izin Usaha Pertambangan Ormas dalam Peraturan Pemerintah Nomor 25 Tahun 2024: Potential Irregularities Of Public Organizations' Mining Business Licenses In Government Regulation No 25 Of 2024 - Adinda Agis Fitria Cahyani (CV Rewang Rencang, 2023)
Mining activities often cause negative impacts, such as environmental pollution, environmental damage, pollution from mining activities, and damage to road access which leads to a conflict problem, whether it is between community conflicts with companies or communities with the government. The purpose of this research is to find out the potential irregularities of the Mining Business License (IUP) ormas after the enactment of Government Regulation Number 25 of 2024. The results of this study are that Article 83A paragraph (1) is contrary to Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining (Minerba Law), this is not in line with the legal principle of lex superior derogate legi inferiori. The potential deviations are lack of experience and competence, potential internal conflicts, weak supervision and regulation, local economic instability, and corruption and abuse of authority. Keywords: Deviations, Mining Business License, Community Organization.